2022
DOI: 10.1111/jcmm.17528
|View full text |Cite
|
Sign up to set email alerts
|

One night of sleep deprivation induces release of small extracellular vesicles into circulation and promotes platelet activation by small EVs

Abstract: Extracellular vesicles (EVs) are emerging as key players in intercellular communication. Few studies have focused on EV levels in subjects with sleep disorders. Here, we aimed to explore the role of acute sleep deprivation on the quantity and functionality of circulating EVs, and their tissue distribution. EVs were isolated by ultracentrifugation from the plasma of volunteers and animals undergoing one night of sleep deprivation. Arterio‐venous shunt, FeCl3 thrombus test and thrombin‐induced platelet aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…This view originates mainly from studies in which the synthetic HMGB1 protein was directly applied to the culture medium of various cells [ 1 , 74 , 75 ]. However, if HMGB1 is released within EVs in vivo as previously predicted [ 2 , 76 ] and shown in the present study, binding to intracellular counterparts of these receptors is more likely after uptake. The width of the interstitium around cell bodies ranges from 38 to 64 nm in the rat brain, smaller than most sEVs, creating an optimal environment for sEVs released to directly contact the large astrocyte membrane surface, ensheathing neuron soma [ 77 ] at the moment they are released, which may also be facilitated with more specific uptake mechanisms [ 71 ].…”
Section: Discussionsupporting
confidence: 77%
“…This view originates mainly from studies in which the synthetic HMGB1 protein was directly applied to the culture medium of various cells [ 1 , 74 , 75 ]. However, if HMGB1 is released within EVs in vivo as previously predicted [ 2 , 76 ] and shown in the present study, binding to intracellular counterparts of these receptors is more likely after uptake. The width of the interstitium around cell bodies ranges from 38 to 64 nm in the rat brain, smaller than most sEVs, creating an optimal environment for sEVs released to directly contact the large astrocyte membrane surface, ensheathing neuron soma [ 77 ] at the moment they are released, which may also be facilitated with more specific uptake mechanisms [ 71 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our research found that after acute 12-hour sleep deprivation, liver metabolism was strongly activated, with heightened catabolic activity and a signi cant increase in various metabolites. Previous studies suggest that a single 6-hour episode or a full night of acute sleep deprivation induces abnormal glucose tolerance, liver insulin resistance [30] and increased risk of thrombosis [31]. Consequently, our results raise a cautionary note for individuals who habitually stay up late, as such behavior not only induces signi cant uctuations in various liver metabolic indicators but also harbors potential detrimental impacts on physical well-being and brain functionality.…”
Section: Discussionmentioning
confidence: 58%
“…However, this short duration is a limitation of our study. Changes in EV properties can be initiated quickly, such as after acute injury or with one night of sleep deprivation (Luo et al., 2023 ; Wang et al., 2022 ). However, we speculate that a longer fasting period (under appropriate clinical supervision) would allow more time for the circulating EV pool to be turned over.…”
Section: Discussionmentioning
confidence: 99%
“…EVs derived from mouse hearts after MI induction promoted pro‐inflammatory behaviour, influenced macrophage polarisation, and aggravated heart injury in recipient mice (Ge et al., 2021 ). In another study, one night of sleep deprivation (in mice) altered circulating EVs to have more pro‐thrombotic effects (Wang et al., 2022 ). Exercise has been shown (in mice) promote mobilisation of EVs from brown adipose tissue which contained cardioprotective miRNAs (Zhao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%